A Comprehensive Approach to Speciation of Lead and Its Contamination of Firing Range Soils: A Review. Issue 4 (19th May 2019) - Dinake, Pogisego; Kelebemang, Rosemary; Sehube, Nicholas
ABSTRACT: Lead pollution of shooting range soils has received tremendous attention in the past few years due to its adverse effects to the environment. High total Pb concentrations have been reported in shooting range soils. Soil physicochemical properties such as pH, organic matter, cation exchange capacity (CEC) and soil moisture have been found to have a strong influence on the transformation of Pb shots. Therefore, it is imperative that the soil physicochemical properties are well understood when investigating the environmental effects of Pb. Total Pb concentration gives a measure of the amount of Pb stored in soil but does not give a true picture of the environmental pollution risk. In their quest to control pollution of shooting range soils from Pb, scientists have applied soil remedial methods such as soil washing, chemical stabilisation and phytoremediation. This review examines the pollution status of shooting range soils from Pb, the effect of soil properties on Pb mobility and bioavailability, the importance of Pb chemical speciation in understanding Pb mobility and shooting range management strategies applied in the control and management of Pb pollution of shooting range soils. This is a holistic review covering literature from 1983 to 2018, a period of 35 years.